Effect of Metformin on Fasting Insulin Levels in Non-Diabetic Obese Patients Over 8 Weeks of Time (Medical Forum Monthly, 2023)
Objective: To determine the effect of metformin on fasting insulin levels in non-diabetic obese patients over 8 weeks of time.Study Design: Prospective Interventional Study Place and Duration of Study: This study was conducted at the Department of Medicine of Al- Nafees Medical College and Hospital, Islamabad from November, 2020 to May, 2021.Materials and Methods: The study was conducted after the hospital’s ethical committee approval, and informed written consent was taken. Patients with obesity having BMI equal to or more than 25 without diabetes mellitus were selected after fulfilling inclusion criteria and sub-categorized on the basis of gender and age. HBA1C and fasting insulin levels were performed. Metformin 1000mg was given to these subjects twice a day for 8 weeks. The fasting insulin levels were repeated after 8 weeks. Collected information was analyzed by using SPSS 23 versionResults: A total of 50 random individuals were selected of which 26 (52%) were males and 24 (48%) were females. The mean age of males and females in the study is 32.640 and 36.250. The mean HBA1C of males and females is 5.464 and 5.308 respectively. The mean weight of males and females before drug use is 88.280 kg and 83.458 kg respectively. The mean weight of males and females after drug use is 85.080 kg and 80.208 kg respectively. The average reduction in fasting insulin levels in individuals from 9.112mIU/mL to 7.215mIU/mL during the period of 8 weeks.Conclusion: It has been concluded from this study that metformin significantly lowers fasting insulin levels in obese non-diabetic patients. Early detection and therapy of the obese adolescent with a family history of type 2 diabetes may interrupt the cycle of weight gain and insulin resistance that leads to glucose intolerance in adulthood.